2006
DOI: 10.2146/ajhp050205
|View full text |Cite
|
Sign up to set email alerts
|

Survey of pharmacist collaborative drug therapy management in hospitals

Abstract: Approximately 50% of respondent hospitals had some pharmacists engaged in CDTM. Although CDTM was perceived as not having a positive financial impact on pharmacy departments, it was perceived as having a positive strategic impact by improving the views of upper administration regarding the value of pharmacists and facilitating implementation of other pharmacy services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…In 2003, 49.7% of pharmacists in the United States performed their pharmaceutical activities according to the Collaborative Drug Therapy Management (CDTM) in hospitals. 25 The CDTM has been frequently The efficacy of our PBPM in warfarin therapy in this study is consistent with the results of CDTM, which has previously been documented. [5][6][7][8][9][10] However, in most of these previous reports, the aims of warfarin therapies were focused on the treatment of AF.…”
Section: Discussionsupporting
confidence: 90%
“…In 2003, 49.7% of pharmacists in the United States performed their pharmaceutical activities according to the Collaborative Drug Therapy Management (CDTM) in hospitals. 25 The CDTM has been frequently The efficacy of our PBPM in warfarin therapy in this study is consistent with the results of CDTM, which has previously been documented. [5][6][7][8][9][10] However, in most of these previous reports, the aims of warfarin therapies were focused on the treatment of AF.…”
Section: Discussionsupporting
confidence: 90%
“…For example, some states may allow initiation of medication therapy (independent prescribing) and others may only allow modification of existing drug therapy (dependent prescribing). 24 An organization must comply with the Pharmacy Practice Act of the state in which it resides when developing a CPA; individual states may also include educational prerequisites, allowable drug classes, quality assurance, and documentation requirements in their regulations that govern use of CPAs.…”
Section: Cpa Definitionmentioning
confidence: 99%
“…These results were particularly surprising because a previously published survey concluded that CDTM was used at about 50% of hospitals in the United States, not distinguishing between adult hospitals and children's hospitals. 7 It appears that CDTM occurs less often in the care of children, regardless of the type of children's hospital. Therefore, some adult hospitals may limit the CDTM to adult patients only and not provide it for their pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 Some surveys have attempted to determine this information. 7,8 Among those surveys was one conducted in 1996, which included results obtained from 713 hospital pharmacy directors. 7 This study found that 56% of hospital pharmacists participated in some form of CDTM at their institution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation